2012
DOI: 10.1007/s00595-011-0115-3
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey on adult type chronic intestinal pseudo-obstruction in surgical institutions in Japan

Abstract: The segments of the diseased bowels should be considered in determining the indications for surgical treatments in CIP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…As in other studies with a similar number of patients, a predominance of females was observed, and most of the cases corresponded to primary CIPO. 4,10,12,13 The average age of our patients at diagnosis was similar to that described in European studies 12 and significantly younger than the age observed in Japanese studies. This is probably due to enrollment of patients with colonic involvement, which appear at an older age.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…As in other studies with a similar number of patients, a predominance of females was observed, and most of the cases corresponded to primary CIPO. 4,10,12,13 The average age of our patients at diagnosis was similar to that described in European studies 12 and significantly younger than the age observed in Japanese studies. This is probably due to enrollment of patients with colonic involvement, which appear at an older age.…”
Section: Discussionsupporting
confidence: 85%
“…In the work by Masaki et al, 4 the distribution was reversed with the colon appearing compromised most frequently, and the least common disorder being the small intestine.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations